A successful chronic care program in Al Ain-United Arab Emirates - Al Husaini Alhusini I; Revel Anthony D; Elkhalid Abdulkarim M; Jaber Tariq M; Al Deen Sanaa; Ahmed Nader M; Abusamak Ahmad M; Nagelkerke Nico JD; Al Ameri Thuraya A; Al Kuwiti Moza H; Al Mukini Lolowa A; Ali Tahira A; et al. (BMC, 2010)
Abstract Background The cost effective provision of quality care for chronic diseases is a major challenge for health care systems. We describe a project to improve the care of patients with the highly prevalent disorders of diabetes and hypertension, conducted in one of the major cities of the United Arab Emirates. Settings and Methods The project, using the principles of quality assurance cycles, was conducted in 4 stages. The assessment stage consisted of a community survey and an audit of the health care system, with particular emphasis on chronic disease care. The information gleaned from this stage provided feedback to the staff of participating health centers. In the second stage, deficiencies in health care were identified and interventions were developed for improvements, including topics for continuing professional development. In the third stage, these strategies were piloted in a single health centre for one year and the outcomes evaluated. In the still ongoing fourth stage, the project was rolled out to all the health centers in the area, with continuing evaluation. The intervention consisted of changes to establish a structured care model based on the predicted needs of this group of patients utilizing dedicated chronic disease clinics inside the existing primary health care system. These clinics incorporated decision-making tools, including evidence-based guidelines, patient education and ongoing professional education. Results The intervention was successfully implemented in all the health centers. The health care quality indicators that showed the greatest improvement were the documentation of patient history (e.g. smoking status and physical activity); improvement in recording physical signs (e.g. body mass index (BMI)); and an improvement in the requesting of appropriate investigations, such as HbA1c and microalbuminurea. There was also improvement in those parameters reflecting outcomes of care, which included HbA1c, blood pressure and lipid profiles. Indicators related to lifestyle changes, such as smoking cessation and BMI, failed to improve. Conclusion Chronic disease care is a joint commitment by health care providers and patients. This combined approach proved successful in most areas of the project, but the area of patient self management requires further improvement.